Myeloproliferative neoplasms - Costa Villela, Neysimelia; Zamperlini, Gustavo; Shimoda Ikeuti, Patrícia; Vasconcelos Gouveia, Roseane; de Castro Resende Franco, Simone; Lopes, Luiz Fernando (JOURNAL OF BONE MARROW TRANSPLANTATION AND CELLULAR THERAPY, 2021)
In addition to the chronic myeloid leukemia (CML) BCR-ABL1+, classic myeloproliferative neoplasms include polycythemia vera, essential thrombocythemia and primary myelofibrosis. These have a very low incidence in the pediatric age group and there is no consensus on treatment in children.